A research proposal: use of the waves of the sea in the port of Pecem-Ceará (Research, Society and Development, 2019)
This article aims to present a research on the progress of the project of the sea wave plant in the port of Pecém in Ceará, analyzing the economic, environmental and social impacts of the implementation of the plant as a renewable alternative energy source. During the research, we intend to be diagnosing in the field how the wave power plant is working, assessing what possible environmental impacts or not the power plant module could cause in the region. In the article, we will explain about the main characteristics of the sea waves and the relevance of investing in the generation of clean energies. The use of wave force is an interesting alternative as energy generation, since it uses a renewable matrix that will not be exhausted and will therefore promote the sustainable development of those who adhere to this form of clean energy generation.